Innovative budget implementation approach in South Nias: organizational commitment as moderator - Halowo Fau, Samanoi; Wau, Marselino; Waoma, Samalua (Enrichment : Journal of Management, 2024)
This study aims to determine the effect of budget participation, budget target clarity and budget realization with organizational commitment as a moderating variable in South Nias Regency. The population in this study were 189 people from 63 OPD Departments / Agencies. The sampling technique used was 28 SKPDs selected using cluster sampling. Thus, the total sample was 84 respondents. This type of research is quantitative research. The analytical tool used is the Likert scale. The results of this study indicate that budget participation and budget target clarity significantly affect budget realization in South Nias Regency. Organizational commitment cannot moderate the effect of budget participation and budget goal clarity on budget realization in South Nias Regency. This study uses descriptive statistical and partial least squares analysis with Smart PLS 4.0 software.